Candidiasis and other oral Fungi - Marwa Husain Abdullah Mohi AL-kahfaji (Zien Journals, 2022)
Candidiasis, often known as oral candidiasis, is the most common mucocutaneous mycosis of the mouth. It is produced by the genus Candida, which is found as a common commensal bacterium in the oral cavity of 53% of the general population. In the oral cavity, 150 species have been isolated, with Candida albicans accounting for 80% of the isolates. Candida albicans can colonize the oral cavity alone or in conjunction with other species. The transition from commensal organism to pathogen is dependent on the intervention of various predisposing factors that alter the oral cavity milieu and favor the appearance of opportunistic infection. The current study provides a review of the literature on the diagnosis of oral candidiasis with the goal of determining when complementary microbiological approaches for diagnosis should be used .due to immunodeficiency viruses and immunosuppressive medications, fungus infections are becoming more widespread. Candidasis is the most common fungus to infect the oral cavity. Candida should be ruled out if identified in isolation without any other clinical symptoms because it can be a common commensal. Candida's pathogenicity is Opportunistic infections are those that arise when the immune system is weakened. Despite the rarity of oral fungal infections they are more unpleasant when they do happen and can possibly result in tissue damage. Cytology and tissue samples can support the clinical diagnosis. When treating oral fungal infections, it is critical to prioritize indications, symptoms, and culture findings.
Keywords: Fungal deep infection; Candida's pathogenicity; oral mycosi